2022
DOI: 10.21203/rs.3.rs-2369262/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An ATP-sensitive phosphoketolase regulates carbon fixation in cyanobacteria

Abstract: Regulation of CO2 fixation in cyanobacteria is important both for the organism and the global carbon balance. Here we show that phosphoketolase in Synechococcus elongatus PCC7942 (SeXPK) possesses a distinct ATP sensing mechanism, which upon ATP drops, allows SeXPK to divert precursors of the RuBisCO substrate away from the Calvin-Benson-Bassham (CBB) cycle. Deleting the SeXPK gene increased CO2 fixation particularly during light-dark transitions. In high-density cultures, the Dxpk strain showed a 60% increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…When ATP level lowers upon cell entering the dark 25 , phosphoketolase can be activated to catalyze X5P cleavage. A more recent report confirmed the allosteric regulation of phosphoketolase by ATP, and further showed an increased phosphoketolase activity during lightdark transitions to brake on the CBB cycle and switch cell metabolism into respiration 26 .…”
Section: Discussionmentioning
confidence: 68%
“…When ATP level lowers upon cell entering the dark 25 , phosphoketolase can be activated to catalyze X5P cleavage. A more recent report confirmed the allosteric regulation of phosphoketolase by ATP, and further showed an increased phosphoketolase activity during lightdark transitions to brake on the CBB cycle and switch cell metabolism into respiration 26 .…”
Section: Discussionmentioning
confidence: 68%
“…Notably, at the optimal concentration of CDs (40 mg L −1 ), the growth rate of Syne cells reached 0.1 h −1 during the exponential growth phase, which was 1.5-fold higher than that of the control group without CDs. As photoautotrophs, Syne cells fix and convert CO 2 into biomass, and they derive energy from photosynthesis for CO 2 fixation and biomass formation 51 . Thus, our results suggest that the CDs enhance the photosystem activity and CO 2 fixation of Syne cells.…”
Section: Resultsmentioning
confidence: 99%
“…In dark heterotrophic conditions, PK is necessary for acetate production from exogenous sugars (Xiong et al, 2015). Recently, it has been revealed that the consumption of sugar phosphates by PK immediately after the light-to-dark transition halts the CBB cycle (Lu et al, 2023). The GAP generated by PK potentially contributes to the accumulation of glycolytic acid intermediates.…”
Section: Discussionmentioning
confidence: 99%